Durability of concrete mixtures with different contents of activated fly ash - Rendon Belmonte, Mariela; Martínez Madrid, Miguel; Martínez Pérez, Rosa Verónica; Peréz Quiroz, José Trinidad (Revista ALCONPAT, 2019)
This article describes properties related to the durability of five different mixtures of concrete with different contents of activated fly ash (AFA) and Portland cement (CPC 40). The measurements carried out were apparent speed of ultrasonic pulse, electrical resistivity, fast ion permeability of chloride and mechanical resistance to compression. The performance of all mixtures proved to be durable, and the development of the electrical resistivity and the decrease in the level of the chloride ion permeability were enhanced by the contents of AFA, although the resistance to compression at higher contents of AFA was minor. The maximum percentage of AFA to comply with the current criteria of durability was 65%.